2013
DOI: 10.1080/19440049.2013.789558
|View full text |Cite
|
Sign up to set email alerts
|

Human aflatoxin exposure in Kenya, 2007: a cross-sectional study

Abstract: Aflatoxins contaminate approximately 25% of agricultural products worldwide. They can cause liver failure and liver cancer. Kenya has experienced multiple aflatoxicosis outbreaks in recent years, often resulting in fatalities. However, the full extent of aflatoxin exposure in Kenya has been unknown. Our objective was to quantify aflatoxin exposure across Kenya. We analysed aflatoxin levels in serum specimens from the 2007 Kenya AIDS Indicator Survey – a nationally representative, cross-sectional serosurvey. KA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 31 publications
(40 reference statements)
4
55
3
2
Order By: Relevance
“…If taking their proposed 4.6 conversion, the AFB-Lys adduct level in our study using GPC study samples is similar to that of Asiki et al (2014). The averaged adduct level is actually higher than the levels found in children from Kikelelwa, Tanzania (0.78 pg mg −1 albumin after conversion by division of 4.6) (Shirima et al 2013;Yard et al 2013). However, the adduct level is still lower than averaged levels found from neighbouring countries, such as Kenya and Tanzania, and West African countries, such as Ghana, Gambia, Benin and Togo (Gong et al 2002(Gong et al , 2012Ofori-Adjei 2012;Shirima et al 2013).…”
Section: Round (Year)mentioning
confidence: 75%
See 2 more Smart Citations
“…If taking their proposed 4.6 conversion, the AFB-Lys adduct level in our study using GPC study samples is similar to that of Asiki et al (2014). The averaged adduct level is actually higher than the levels found in children from Kikelelwa, Tanzania (0.78 pg mg −1 albumin after conversion by division of 4.6) (Shirima et al 2013;Yard et al 2013). However, the adduct level is still lower than averaged levels found from neighbouring countries, such as Kenya and Tanzania, and West African countries, such as Ghana, Gambia, Benin and Togo (Gong et al 2002(Gong et al , 2012Ofori-Adjei 2012;Shirima et al 2013).…”
Section: Round (Year)mentioning
confidence: 75%
“…Compared with other African countries, the averaged AFB-Lys level found in this study was among those lower levels reported. Yard et al (2013) suggested that the estimated AFB-Lys adduct values from the ELISA method is typically 4.6 times higher than that from the HPLC-fluorescence measurement. If taking their proposed 4.6 conversion, the AFB-Lys adduct level in our study using GPC study samples is similar to that of Asiki et al (2014).…”
Section: Round (Year)mentioning
confidence: 99%
See 1 more Smart Citation
“…Debido a la alta prevalencia de casos de aflatoxicosis documentados en el país, en el 2013 se cuantificó la exposición de aflatoxinas a través de un estudio serológico y epidemiológico transversal. Se detectaron aductos de AFB1 en el 78% de las muestras de suero y se concluyó que la exposición a aflatoxinas es un problema de salud pública en Kenia, el cual puede generar impacto en la salud humana (70).…”
Section: Evaluación De La Exposiciónunclassified
“…In einer Querschnittstudie mit 600 Probanden in Kenia wurde AFB1-Lys in 78 % aller Blutproben mit Werten zwischen 0,02 (Detektionslimit) und 9,52 ng AFB1-Lys/ml detektiert. Im Gegensatz dazu zeigten nur 1,3 % aller Blutproben von 2104 US-Einwohnern messbare Konzentrationen von AFB1-Lys zwischen 0,02 und 0,2 ng AFB1-Lys/ml [19]. Durch Bestimmung der Lysinaddukte mittels ELISA oder LC-MS/MS wurden Zusammenhänge zwischen der Aufnahme von AFB1 und dem Auftreten von Tumoren in der Leber [20] und der Gallenblase [21] sowie einem verminderten Wachstum von Kindern gezeigt [22].…”
Section: Aflatoxin Bunclassified